P Penerapan algoritma equivalence class transformation (eclat) dalam pencarian adverse event obat simvastatin - Ali, Ali Husin Siregar; Alwis, Alwis Nazir; Iis, Iis Afrianty; Elvia, Elvia Budianita; Fitri, Fitri Insani (Computer Science and Information Technology, 2023)
Cholesterol is a type of fat that circulates in the bloodstream and has an important role in body functions. However, excess cholesterol levels can cause various problems in the body that interfere with the heart, blood vessels, and brain systems. Simvastatin is a lipid-lowering drug in the blood that can reduce cholesterol. In this study, an adverse event was conducted which is an unwanted event in the world of health in the consumption of simvastatin drugs using the Equivalence Class Transformation (ECLAT) algorithm. The data used came from the Food and Drug Administration (FDA) which amounted to 22560 data. Data is managed by the Knowledge Discovery in Databases (KDD) process which goes through several stages, namely data selection, data processing, data transformation, and data mining. Test results are measured based on the lift ratio value which aims to measure the validity of the resulting rule. The test was conducted using a minimum support value of 0.001 and obtained the best lift ratio value of 886.00. In the combination of 2 items, the best rule is "if the duration of therapy is 98 months, it results in acute kidney injury" from 1451 rules with a processing time of 2.70 seconds. The combination of 3 items produces 39 rules with a processing time of 4.46 seconds with the best rule being "if the duration of therapy is 142 months and indicated ill-defined disorder then results in increased blood creatine". The combination of 4 items only produced 18 rules with the best rule being "if sex f, duration of therapy < 1 month and indicated abnormal coronary arteriogram then resulted in anaphylactic shock" in a processing time of 3.45 seconds.